Process analysis and concepts for thermal treatment of waste - Haindl, Simon (My University, 2016)
In order to make a reasonable process proposal regarding the thermo-chemical treatment of waste-streams provided by the STENA Metall, a detailed literature review of different processes and state of art reactors was done. The CHEMKIN PRO simulation tool was used in order to estimate the behaviour of product formation from processing plastic in a thermo-chemical reactor with respect to temperature and the reactor atmosphere. For the process determination, optimal process conditions of pyrolysis and gasification processes are investigated to recover valuable organic and inorganic materials. Different reactors like circulating fluidized beds (CFB) and rotary kilns are examined to prove their technical and economical feasibility. Various waste-streams like SLF and WEEE are assessed by their amount of valuable metals, but also their hazardous elements. Within the CHEMKIN PRO simulation the highest yield of different chemicals and fuels is investigated. The chemicals with the highest mole-fractions are hydrogen, methane, ethylene, ethane, propene and benzene. High temperatures increase the formation of hydrogen, methane and benzene, whereas low temperatures increase the formation of ethylene, ethane and propene. High ratios of steam in the reaction atmosphere increase the production of hydrogen, methane and benzene, whereas low ratios of steam increase the production of ethylene, ethane and propane. After investigations of the influence of different parameter with the CHEMKIN PRO simulation and the evaluation of different process parameter a process layout for selected waste-streams is proposed.
Keywords: Energiteknik; Hållbar utveckling; Energi; Energy Engineering; Sustainable Development; Energy